Implementing the four-component instructional design model in professional development programs: a systematic review with a focus on teachers - Neck, Melanie; Leuders, Timo; Reinhold, Frank (Frontiers in Education, 2025)
The four-component instructional design (4C/ID) model is designed to support complex learning by facilitating the transfer of theoretical knowledge into practice. This study presents a systematic research synthesis on the implementation of the 4C/ID model in training programs with a special focus on teachers. Specifically, we investigate how the four components and 10 steps of 4C/ID are applied in training programs, for which professional fields and real-life tasks it is used, the concreteness of the instructional design, and the effects on learning. A special focus is on the model's implementation in teacher education. A systematic database search following PRISMA guidelines yielded 55 relevant studies, which were systematically coded and analyzed. Surprisingly, we found only a few papers of n = 11 on in-service training with 4C/ID for teachers. Our findings indicate that many studies referencing the 4C/ID model lack detailed descriptions of its implementation. To complement our qualitative synthesis, we conducted a quantitative subanalysis, applying a multilevel meta-analysis to estimate the overall effect size of training programs based on pre-post comparisons. The results yielded a moderate positive effect (g = 0.76, SE = 0.31, p = 0.014), suggesting that the 4C/ID model has a meaningful impact on learning outcomes. These findings underscore the need for more structured reporting and further research on the implementation of 4C/ID, particularly in teacher education.